2021
DOI: 10.1212/wnl.0000000000011050
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cerebral Small Vessel Disease and Cognitive Decline After Intracerebral Hemorrhage

Abstract: Objective:We sought to determine whether MRI-based Cerebral Small Vessel Disease (CSVD) burden assessment, in addition to clinical and CT data, improved prediction of cognitive impairment after spontaneous Intracerebral Hemorrhage (ICH).Methods:We analyzed data from ICH survivors enrolled in a single-center prospective study. We employed three validated CSVD burden scores: global, cerebral amyloid angiopathy (CAA)-specific, hypertensive arteriopathy (HTNA)-specific. We quantified cognitive performance by admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 30 publications
1
81
0
Order By: Relevance
“…Developmental defects in the middle layer of the arterial wall, arteriosclerosis and hypertension are three important factors for cerebral hemorrhage, among which hypertension is an important independent risk factor for cerebral hemorrhage [19]. Although the pathogenesis of HICH is not yet complete, it is currently believed that hypertension is an important basis for its pathogenesis, that is, hypertension induces mechanical stress changes to act on endothelial cells (ECs), causing a series of pathological changes, resulting in vascular wall damage [20]. However, the molecular mechanism of HICH is less studied.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental defects in the middle layer of the arterial wall, arteriosclerosis and hypertension are three important factors for cerebral hemorrhage, among which hypertension is an important independent risk factor for cerebral hemorrhage [19]. Although the pathogenesis of HICH is not yet complete, it is currently believed that hypertension is an important basis for its pathogenesis, that is, hypertension induces mechanical stress changes to act on endothelial cells (ECs), causing a series of pathological changes, resulting in vascular wall damage [20]. However, the molecular mechanism of HICH is less studied.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted a validated CAA-SVD scoring reflexive of total CAA pathological burden in the brain ( 4 , 20 ). Briefly, each marker category was scored on a 0–6 scale.…”
Section: Methodsmentioning
confidence: 99%
“…One point (each) was scored for ≥ 20 BG PVSEs or ≥ 5 lacunes. C 2 score was equivalent to the global cerebral SVD score developed to represent total SVD burden of both HA and CAA pathologies ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was pointed out, in an accompanying editorial, 123 that lobar CMBs and presence of the APOE e4 allele were also associated with delayed dementia. Pasi et al 124 reported an enhanced risk of cognitive decline, following ICH, was associated with a higher global cerebral SVD score.…”
Section: White Matter Degenerationmentioning
confidence: 99%